2020
DOI: 10.1002/wer.1351
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of soluble recalcitrant compounds in commercial thermal hydrolysis digestates

Abstract: Solid residues such as primary sludge (PS), waste activated sludge (WAS), and food waste (FW) can be stabilized through anaerobic digestion (AD). Application of the thermal hydrolysis process (THP) prior to AD results in several benefits in AD and dewatering. However, soluble recalcitrant compounds associated with Maillard reactions have been identified after THP which can impact downstream processes and water discharge limits. In this study, the soluble colloidal chemical oxygen demand, color, ultraviolet abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These dark coloured compounds can compromise the stability of downstream biological processes and water discharge limits. The presence of these compounds was studied by Svennevik et al [20], who reported that a small increase in water effluent COD concentration may be associated with the presence of recalcitrant substances derived from THP. Table 2 presents a list of technologies that are commercially available.…”
Section: Processmentioning
confidence: 99%
See 2 more Smart Citations
“…These dark coloured compounds can compromise the stability of downstream biological processes and water discharge limits. The presence of these compounds was studied by Svennevik et al [20], who reported that a small increase in water effluent COD concentration may be associated with the presence of recalcitrant substances derived from THP. Table 2 presents a list of technologies that are commercially available.…”
Section: Processmentioning
confidence: 99%
“…The whole sludge line and dewatering operations, along with the biogas valorisation section, are considered. Equation (20) allows the estimation of the thermal power of the global process.…”
Section: Energy Balance Of the Total Processmentioning
confidence: 99%
See 1 more Smart Citation